Lab manual for psychological research / by Dawn M. McBride and J. Cooper Cutting - "McBride, Dawn M." (New Delhi, 2013)
This book explain the research interests include automatic forms of memory, false memory, prospective memory, and forgetting. In addition to research methods, she teaches courses in introductory psychology, cognition and learning, human memory, and a graduate course in experimental design.
Keywords: Psychology-Research-Methodology